Dominance of Chaetoceros sp. and occurrence of Noctiluca scintillans bloom in Villareal Bay, Samar Desiree Ann B. Cabangon; Leni G. Yap-Dejeto, adviser. - Cabangon, Desiree Ann B.; Yap-Dejeto, Leni G. (2024)
Villareal Bay, situated within the Samar province in the Eastern Visayas region of the Philippines, serves as a vital ecosystem influenced by sediment-laden waters from various riverine and fluvial networks. The bay's significance extends to the livelihoods of local communities, particularly through mussel cultivation. Despite this importance, research on phytoplankton, the primary producers of marine ecosystems, remains limited in the area. The study aimed to characterize the phytoplankton community in Villareal Bay, employing a 1 m length, 20-µm mesh size plankton net for qualitative analysis and I L samples via Van Dorn water sampler for quantitative analysis. Over the period from August 2023 to January 2024, 55 genera were identified, revealing a total average cell density of 9.7 ± 0.47 x 10^5 cells/L. The calculated indices for the phytoplankton community showed average values of 2.65±0.32 for species diversity (H'), 0.32±0.11 for evenness (J), and 0.24 ±0.07 for richness (D). Dominant taxa included Noctiluca scintillans, Chaetoceros sp., Bacteriastrum sp., Pleurosigma sp. Pseudo-nitzschia sp., and Cylindrotheca sp. The diatom, Chaetoceros sp.. consistently exhibited the highest average cell density over a four-month period from August to November 2023. In January 2024, a bloom of the dinoflagellate green N. scintillans occurred, recording an average cell density of 8.1 ± 0.11 x 10^4 cells/L. This bloom contributed to the overall phytoplankton density in January which also had the highest average cell density among all sampling months, with a value of 1.7 ± 0.22 x 10^5 cells/L. Additionally, the study identified 13 potentially harmful phytoplankton species present in the bay, warranting further investigation and discussion. This research underscores the importance of documenting and understanding phytoplankton dynamics in Villareal Bay for both local management strategies and broader ecological studies.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.